IMPLEMENTATION OF THE PROMOTIONAL MIX STRATEGY ON YAMAHA MOTORS TO PURCHASE DECISIONS DURING THE COVID-19 PANDEMIC AT PT ALFA SCORPII - Dina Nadilla (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
Due to the phenomenon or impact of the Covid-19 pandemic, the automotive industry is deteriorating and we know that in the current era of globalization all companies must face competition in marketing their products and services. This is one of the things that companies can do by implementing a promotional mix strategy. The purpose of this study is to provide an overview of the form and impact of the promotion carried out by PT Alfa Scorpii Medan on Yamaha products. The data collection method in this study used quantitative methods by distributing questionnaires to respondents measured by a Likert scale, then collecting data that met the validity and reliability requirements and then tested using multiple regression analysis.